Optimizing Sand-Based Biofilm Biosorption for Copper (Cu) Mitigation: Mechanisms, Optimal Conditions, and Environmental Implications - Rosna; Zaeni, Ahmad; Kadidae, Laode; Zainal Syam Arifin (Journal of Pharmaceuticals and Natural Sciences, 2025)
Copper (Cu) pollution from industrial wastewater has emerged as a critical environmental issue due to its toxicity, bioaccumulation, and persistence in aquatic ecosystems. Conventional methods for heavy metal remediation often fail to address the dual challenge of high costs and environmental sustainability, necessitating alternative approaches. This study explores the use of sand-based biofilms for the biosorption of Cu ions, leveraging the natural ability of biofilms to adsorb and immobilize heavy metals. The research focuses on optimizing biosorption conditions, including contact time, initial Cu concentration, and pH, while evaluating the broader impacts on water quality parameters such as Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), and Total Dissolved Solids (TDS). The experimental results demonstrated that biosorption efficiency peaked at a contact time of 1 day, an initial Cu concentration of 100 mg/L, and a pH of 8. At these optimal conditions, the biofilm achieved a biosorption capacity of 39.7 mg/L for Cu ions. Moreover, the treatment significantly improved water quality, reducing COD by 77.06%, BOD by 78.92%, and TDS by 30%. The mechanism of biosorption was influenced by the availability of functional groups within the extracellular polymeric substance (EPS) of the biofilm, which provided binding sites for Cu ions. The influence of pH was particularly notable, as it regulated the ionic interactions between Cu2+ and the biofilm matrix. This study not only confirms the effectiveness of biofilm-based biosorption for heavy metal mitigation but also highlights its dual role in reducing organic and inorganic pollutants in wastewater. The use of sand as a substrate for biofilm growth adds an element of scalability and economic feasibility, making it an attractive solution for industrial applications. The findings underscore the potential of this eco-friendly approach to contribute to sustainable wastewater management, addressing both environmental and public health concerns associated with heavy metal contamination. Future research could explore the application of this method for other heavy metals and its integration into existing wastewater treatment systems.